A Critical Review of the New Theory of Consumer Society in Japan - 강문원; 류영진; 정현일 (Journal of Global and Area Studies , 8(2), 2024)
This study presents a critical review of the new theory of consumer society in Japan (Mamada, 2016, and others). The theory claims that dematerialism is starting to dominate consumption behaviors in Japan and Japanese consumers strongly demand spiritual value from consumption. This new theory is important because the optimistic view of green consumerism is spreading widely in Japan (Nomura, 2023). Our analysis reveals limitations in the practical application and theoretical foundation of this theory. In this study, based on Inglehart’s post-materialism 4- and 12-index analyses, we prove that it is wrong to claim that dematerialism dominates a significant part of consumer behaviors in Japan now. Furthermore, the theory conflates cultural consumption with the consumption of cultural goods, overlooks the material basis of information, and exhibits limitations in agent-based modeling. We further identify several illogical leaps and exaggerations in the new theory, which highlights that environmental sustainability is a research agenda that requires interdisciplinary approaches. KCI Citation Count: 0